Autosomal dominant Robinow syndrome associated with a novel DVL3 splice mutation. Issue 4 (25th March 2018) - Danyel, Magdalena; Kortüm, Fanny; Dathe, Katarina; Kutsche, Kerstin; Horn, Denise
Abstract : Robinow syndrome is a clinically and genetically heterogeneous disorder characterized by mesomelic limb shortening, distinctive facial features, and variable oral, cardiac, vertebral, and urogenital malformations. We identified the novel de novo splice acceptor mutation c.1715‐2A > C in DVL3 in a 15‐year‐old female patient with typical features of Robinow syndrome. By studying DVL3 transcripts in this patient, we confirmed expression of both wild‐type and mutant alleles. Mutant DVL3 mRNAs were found to harbor a deletion of four nucleotides at the beginning of exon 15 and encode a protein product with a distinct −1 reading‐frame C‐terminus. The data demonstrate that mutant DVL3 proteins associated with Robinow syndrome show truncation of the C‐terminus and share 83 novel amino acid residues before the stop codon confirming highly specific DVL3 alterations to be associated with this syndrome. The phenotype of the Robinow syndrome‐affected female reported here is typical as she shows mesomelia and mild hand anomalies as well as characteristic facial anomalies. She also exhibited a supraumbilical midline abdominal raphe which has not been observed in other patients with Robinow syndrome. In contrast to the clinical data of four previously reported individuals with DVL3 ‐related Robinow syndrome, short stature was not present in this individual at the age of 15 years. These findings expand the clinical spectrum of Robinow syndrome associated with DVL3 mutations. To date, comparison of clinical data of DVL3 mutation‐positive individuals with those of patients with genetically different forms did not allow delineation of gene‐specific phenotypes.